Factors Influencing Tax Evasion from a Global Perspective in the Light of Gender - McGee, Robert W.; Shopovski, Jovan; Bolek, Monika (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The goal of this paper is to analyze tax evasion with special emphasis on gender. Factors influencing tax noncompliance such as age, income, education, confidence in government, political scale and religiosity are analyzed. Methodology: Tax evasion is analyzed based on the most recent (Wave 7) World Value Survey data with the significance of differences between respondents, correlation and regression models analysis. Results of the research: It has been found that there are significant differences between the global approach and groups of males and females when the acceptance of cheating on taxes is taken into consideration. The analysis of groups reflected the fact that all factors influence respondents in the same way without distinguishing between males and females.